2001
DOI: 10.2174/1381612013397735
|View full text |Cite
|
Sign up to set email alerts
|

Role of Biotransformation in Conceptal Toxicity of Drugs and Other Chemicals

Abstract: Many developmental toxicants and teratogens require prior metabolism to reactive species or free radicals to exert toxicity. Thus the knowledge of conceptal biotransformation is absolutely critical in understanding toxicity of these chemicals. Due to extremely low content of cytochrome P450 in the embryo and other conceptal tissues, the research focus in recent years has steadily shifted toward enzymes capable of peroxidative oxidation of xenobiotics. At least three enzymes viz. lipoxygenase, peroxidase and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 172 publications
(284 reference statements)
1
5
0
Order By: Relevance
“…The results from X‐ray analysis agree with other observations made so far about LOX as a versatile biocatalyst for biotransformation of endobiotics and xenobiotics (see review articles8, 37). It might also provide some hints as to why the kinetic studies of LOX‐3 inhibition by quercetin38 show competitive and linear behavior on a Lineweaver–Burke plot, but only to a ∼2 μ M concentration, and at 2.5 μ M it becomes nonlinear.…”
Section: Resultssupporting
confidence: 88%
“…The results from X‐ray analysis agree with other observations made so far about LOX as a versatile biocatalyst for biotransformation of endobiotics and xenobiotics (see review articles8, 37). It might also provide some hints as to why the kinetic studies of LOX‐3 inhibition by quercetin38 show competitive and linear behavior on a Lineweaver–Burke plot, but only to a ∼2 μ M concentration, and at 2.5 μ M it becomes nonlinear.…”
Section: Resultssupporting
confidence: 88%
“…This activity may be increased if hydroperoxide fatty acid is substituted by H 2 O 2 . The co‐oxidation of hydrogen donors, drugs, mutagens, carcinogens, pesticides and several chemicals by lipoxygenases from different sources has been established, and the possibility that xenobiotic oxidation mediated by lipoxygenase may occur at biologically significant rates has been suggested [2].…”
Section: Introductionmentioning
confidence: 99%
“…PGS is present in high concentrations in the kidney (Moldéus et al, 1982;Potter and Hinson, 1987b;Lock and Reed, 1998). Immunohistochemical localization studies have also revealed the presence of PGS in high activity in mouse embryos (Parman et al, 1999;Kulkarni, 2001).…”
Section: Discussionmentioning
confidence: 99%